1990
DOI: 10.7748/ns.5.5.36.s44
|View full text |Cite
|
Sign up to set email alerts
|

Empathy, anxiety and transcultural nursing

Abstract: Kem Louie, in a descriptive study, investigates the relationship of empathy and anxiety of nursing students and their attitudes towards patients from ethnic minority groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In three studies, researchers examined the relationship between empathy and attitudes to patients (Astrom et al. 1990, 1991, Louie 1990). Louie (1990) reported a null correlation, although two of the five empathy subscale scores were related to students’ attitudes towards patients from minority ethnic groups ( P < 0·05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In three studies, researchers examined the relationship between empathy and attitudes to patients (Astrom et al. 1990, 1991, Louie 1990). Louie (1990) reported a null correlation, although two of the five empathy subscale scores were related to students’ attitudes towards patients from minority ethnic groups ( P < 0·05).…”
Section: Resultsmentioning
confidence: 99%
“…In three studies, researchers examined the relationship between empathy and attitudes to patients (Astrom et al 1990, 1991, Louie 1990). Louie (1990) reported a null correlation, although two of the five empathy subscale scores were related to students' attitudes towards patients from minority ethnic groups (P < 0AE05). In another two studies, it was found that higher empathy was associated with more positive attitudes towards patients with dementia and less burnout (r = À0AE19 to À0AE32; Astrom et al 1990Astrom et al , 1991.…”
Section: Empathy and Other Variablesmentioning
confidence: 99%
“…Research mto cultural knowledge features m two papers Felder (1990) and Louie (1990) Felder (1990 set out to mveshgate the effed of cultural diversity m nursing education, wble Louie (1990) reports on a descnptive study which set out to mveshgate the relahonsbp of empathy and anxiety of nursing students and their athtudes towards pahents from ethnic mmonty groups Morse & Enghsh (1986) performed a content analysis of seven basic nursing books used by first-year students and eonduded that the uiadequacy of the texts was unfortunate They urged authors to consult with experts m transcultural nursing m order to provide the best methods to rectify the omission The need for nurses to have a good knowledge base and background wbeh equips them to answer the nght questions is explamed by Stokes (I99I), who feels that the work of Lemmger (quoted m the introduehon) ignores other problems and issues such as race, raasm, religion, pohhcs, employment and unemployment DeSanhs (1988) urges a broadenmg of transcultural nursmg to make a sigmficant contnbution at an internahonal level Tbs is based 'on the understanding that most world health problems are not cultural or medical, but social, pobhcal and economic', cuid that 'the infrastmcture providing the actual health care to the conmfiumty is heavily dependent upon governmental suprastmcture for support and progress'…”
Section: Researchmentioning
confidence: 99%